Implementation of guided inquiry learning model to train students' critical thinking skills on reaction rate topic - Syafira Humairoh; Bertha Yonata (Jurnal Pijar Mipa, 2022)
This research describes students’ critical thinking skills by implementing guided inquiry learning models in matter reaction rate, including the syntax implementation of guided inquiry learning models, student activities, critical thinking skills, and cognitive learning outcomes. Students in class XI-IPA 4 SMA Kemala Bhayangkari 1 Surabaya were the study’s subjects. This study uses a pre-experimental design with a One-Group Pretest Posttest Design. The data obtained were analyzed using quantitative analysis methods. It can be concluded that (1) 2 meetings showed an average percentage of 88.84% and 94.64%, which is included in the very good criteria. (2) Relevant students’ activities that appear in the learning process in meetings 1 and 2 respectively 86.67%, 93.33%, and irrelevant activities that appear in the learning process in meetings 1 and 2 respectively 13.33% and 6.67%. (3) The average value of N-gain on the interpretation indicator of 0.80 (high), analysis of 0.81 (high), inference of 0.72 (high), and explanation of 0.86 (high) indicates that students’ critical thinking skills have improved. (4) Students’ cognitive learning outcomes show that 27 of 32 students completed or 84.37%, and five students did not complete or 15.63%.